Heating of the intracluster medium by quasar outflows - Nath, Biman B.; Roychowdhury, Suparna (Monthly notices of the Royal Astronomical Society, 2002)
We study the possibility of quasar outflows in clusters and groups of galaxies heating the intracluster gas in order to explain the recent observation of excess entropy in this gas. We use the extended Press–Schechter formalism to estimate the number of quasars that become members of a group or cluster of a given mass and formation epoch. We also estimate the fraction of mechanical energy in the outflows that is imparted to the surrounding medium as a function of the density and temperature of this gas. We finally calculate the total amount of non-gravitational heating from such outflows as a function of the cluster potential and formation epoch. We show that outflows from broad absorption line and radio-loud quasars can provide the required amount of heating of the intracluster gas. We find that in this scenario most of the heating takes place at z∼1–4, and that this ‘pre-heating’ epoch is at lower redshift for lower-mass clusters.